2019
DOI: 10.1002/aenm.201803380
|View full text |Cite
|
Sign up to set email alerts
|

Operando Quantification of (De)Lithiation Behavior of Silicon–Graphite Blended Electrodes for Lithium‐Ion Batteries

Abstract: to an unstable solid electrolyte interphase (SEI) [4][5][6][7] and large volumetric changes that lead to particle pulverization and loss of electrical contact between the active particles and the current collector. [8][9][10][11][12] Several approaches are being pursued to address these challenges, which include the following: electrolyte additives to improve SEI integrity, [5,7] electrode binders with enhanced mechanical [13] and chemical properties, [6] morphological engineering of Si particles (nanowires, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 33 publications
9
103
0
Order By: Relevance
“…During charging of the Si/C composite, the graphite particles are most likely preferentially lithiated before the Si compound (see Figure a, c–e for model). Thermodynamically, Si should be lithiated before graphite . However, charging at a high rate of 0.5 C moves the system away from the equilibrium situation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During charging of the Si/C composite, the graphite particles are most likely preferentially lithiated before the Si compound (see Figure a, c–e for model). Thermodynamically, Si should be lithiated before graphite . However, charging at a high rate of 0.5 C moves the system away from the equilibrium situation.…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al. recently investigated Si/C composite anodes (15 % Si) in half cells by using energy‐dispersive XRD . For coin half cells, they found that nanometer‐sized Si was alloying before the lithiation of graphite at low C‐rates …”
Section: Introductionmentioning
confidence: 99%
“…Since the lithiation/delithiation behaviors of Si and carbon components in mixed electrodes are still unclear, in situ XRD has been applied to understand the structural changes in two components in Si‐composite anodes during charge/discharge. As shown in Figure , aided by an additional pure graphite (Gr) electrode study, Yao et al investigated the lithiation behavior of Gr in a mixed electrode. The average voltage plateaus of Gr in pure Gr electrodes were lower than those in Si–Gr electrodes (Figure A,B), indicating that the addition of Si reduced the lithiation overpotential of Gr components.…”
Section: Applications Of Advanced Characterization Methods To Siliconmentioning
confidence: 99%
“…Labels G1–G6 and Si1–Si3 next to the XRD spectra designate data taken at voltages corresponding to the same labels in the electrochemical cycling plots. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Applications Of Advanced Characterization Methods To Siliconmentioning
confidence: 99%
“…Due to the lithium storage mechanism of SnO 2 which is a combination of the alloying–dealloying reaction and conversion reaction, the working voltage of SnO 2 (≈1.0 V vs Li/Li + ) is higher than alloying reaction‐type anodes (e.g., silicon (Si, ≈0.4 V vs Li/Li + ), germanium (Ge, ≈0.5 V vs Li/Li + ), and tin (Sn, ≈0.6 V vs Li/Li + )), but lower than conversion reaction‐type anodes (e.g., transition metal oxides TMOs (M = Mn, Fe, Co, Ni, Cu, etc., TC), ≈1–2 V vs Li/Li + ) . The moderate working voltage of the SnO 2 anode (i.e., ≈1.0 V) can effectively inhibit the generation of lithium dendrites to improve the safety of LIBs; additionally, it results in an appropriate output voltage of the full LIB cells and prevents the decomposition of organic electrolytes which occurs at high potentials …”
Section: Introductionmentioning
confidence: 99%